2022
DOI: 10.1136/bmjopen-2022-067812
|View full text |Cite
|
Sign up to set email alerts
|

Peer-support interventions for women with cardiovascular disease: protocol for synthesising the literature using an evidence map

Abstract: IntroductionThe leading cause of death for women is cardiovascular disease (CVD), including ischaemic heart disease, stroke and heart failure. Previous literature suggests peer support interventions improve self-reported recovery, hope and empowerment in other patient populations, but the evidence for peer support interventions in women with CVD is unknown. The aim of this study is to describe peer support interventions for women with CVD using an evidence map. Specific objectives are to: (1) provide an overvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…When affected by false information, patients will have di culties developing healthy behaviors [14], resulting in kinesophobia. Many studies of peer-support models have indicated the need for a formally trained disease expert in peer-support groups [15,16]. An early activity bene ciary can provide useful, enriching, and positive experiences.…”
Section: Discussionmentioning
confidence: 99%
“…When affected by false information, patients will have di culties developing healthy behaviors [14], resulting in kinesophobia. Many studies of peer-support models have indicated the need for a formally trained disease expert in peer-support groups [15,16]. An early activity bene ciary can provide useful, enriching, and positive experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Reference lists of relevant studies also were reviewed. 57 Search strategies were adapted by selecting relevant CVD terms (IHD, heart failure, stroke) from a previous search strategy 61 that was drafted in MEDLINE using Ovid by an information specialist, was peer reviewed by a second information specialist, and then was translated using each database platform's command language, controlled vocabulary, and appropriate search fields. One review author (M.P.)…”
Section: Methodsmentioning
confidence: 99%